Implementation of Religious Court Judge's Decisions in Children by Husband Post Divorce - Abdul Rifai; Husen Alting; Baharuddin Hi; Rusdin Alauddin (LEGAL BRIEF, 2022)
Children are a mandate in the hands of their parents and a clean heart is a very valuable gem. The presence of children in a family is a complement to the happiness of a marriage. Among the legal consequences of breaking up a marriage is the issue of children, because after the divorce of both parents, their rights will not be reduced to get all their needs. Formulation of the Problem What are the legal consequences for a father who does not carry out the judge's decision on the obligation to support children after divorce, How is the problem with submitting the decision of the Religious Court judge regarding the obligation to support the child after the divorce and What is the ideal concept of completing the execution of the decision of the Religious Court which is not carried out by the parents? (father) regarding his obligation to support children after divorce. The approach method used in this study is normative, with primary and secondary data approaches. The impact of the father's obligation not to carry out the court's decision Article 16 PP No. 53 of 2010. The obligation to give part of the salary to the ex. Decree of the Head of BKN No: K.26-30/V.99-6/99 Regarding the explanation of the obligation to give part of the salary to ex-wife and children. The problem of delivering the decision of the judge of the religious court regarding the obligation to support children in divorce includes the problem of the execution of the obligation to provide for the father for the maintenance of the child after the divorce. The petitioner for execution does not know what property the respondent owns. The father is unable to carry out the decision regarding the obligation to support the child on the grounds that he does not have property. The ideal concept of settlement includes Efforts in carrying out the execution of child support, guaranteeing husband's property, execution costs charged to the respondent.